2012
DOI: 10.1007/s10608-012-9456-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Changes in Depressive Symptoms from Pregnancy to Postpartum: The Role of Brooding Rumination and Negative Inferential Styles

Abstract: The current study examined the role of cognitive factors in the development and maintenance of depressive symptoms from pregnancy into the postpartum period. One hundred and one women were assessed for levels of rumination (brooding and reflection), negative inferential styles, and depressive symptoms in their third trimester of pregnancy and depressive symptom levels again at four and eight weeks postpartum. We found that, although none of the three cognitive variables predicted women’s initial depressive rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…It would be of value for future studies to examine the extent to which home practice predicts protection from relapse and to examine specific putative mechanisms, such as rumination and decentering. A growing body of research suggests that rumination may play a role in perinatal depression (Barnum, Woody, & Gibb, 2013; O’Mahen, Flynn, & Nolen-Hoeksema, 2010). Studies in the general population have found that rumination decreased during MBCT for formerly depressed individuals (Michalak, Holz, & Teismann, 2011; Shahar, Britton, Sbarra, Figueredo, & Bootzin, 2010) and that post-treatment rumination predicted depressive relapse (Michalak et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It would be of value for future studies to examine the extent to which home practice predicts protection from relapse and to examine specific putative mechanisms, such as rumination and decentering. A growing body of research suggests that rumination may play a role in perinatal depression (Barnum, Woody, & Gibb, 2013; O’Mahen, Flynn, & Nolen-Hoeksema, 2010). Studies in the general population have found that rumination decreased during MBCT for formerly depressed individuals (Michalak, Holz, & Teismann, 2011; Shahar, Britton, Sbarra, Figueredo, & Bootzin, 2010) and that post-treatment rumination predicted depressive relapse (Michalak et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted, however, that in only 41.6% (n = 26) of cases the follow-up was conducted after delivery. Assessing depressive rumination during the third trimester of pregnancy in 101 women, Barnum et al (2013) found that the coping style was not predictive of short-term depressive responses (baseline to 1-month postpartum), but that it did predict longer-term symptom changes (baseline to 2-months postpartum). Finally, in a study by Müller et al (2013) prepartum rumination did not predict postpartum depressive symptoms five weeks after childbirth.…”
Section: Dampening Of Positive Affect Predicts Postpartum Depressive mentioning
confidence: 96%
“…Considering all the above, depressive rumination during pregnancy is taken to be predictive of higher levels of postpartum depressive symptoms, which is in line with the general literature documenting a predictive association between rumination and depression. Arguably, postpartum symptoms may be limited to longer-term reactions (≥2 months postpartum; Barnum et al 2013), while appearing less relevant in the immediate postpartum period (Barnum et al 2013;Müller et al 2013). Also, the handful of studies conducted so far are limited by their relatively small sample sizes (N<=100) as well as by the fact that none of the studies took prior history of clinical depression into account.…”
Section: Dampening Of Positive Affect Predicts Postpartum Depressive mentioning
confidence: 99%
“…The findings of the above-mentioned study by Barnum et al [25] also speak to the issue of whether RNT maintains perinatal psychological distress. Specifically, rumination (reported in the third trimester) predicted change in depression symptoms (from third trimester to 8 weeks post-partum).…”
Section: Potential Roles Of Rnt In the Perinatal Contextmentioning
confidence: 99%
“…Moreover, such studies have yielded conflicting findings: some have demonstrated that RNT is predictive, while others have reported no such relationship [21]. For example, Barnum et al [25] found that levels of rumination (brooding) predicted increases in depression symptoms from the third trimester to 8 weeks (but not 4 weeks) post-partum. Raes et al [26] reported that rumination did not predict levels of post-partum depression at 12 or 24 weeks when baseline depression and history of depression were controlled.…”
Section: Potential Roles Of Rnt In the Perinatal Contextmentioning
confidence: 99%